1999
DOI: 10.1097/00001756-199907130-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BDNF and NT-3 on hair cell survival in guinea pig cochlea damaged by kanamycin treatment

Abstract: The aim of this study was to determine whether neurotrophic factors such as brain derived neurotrophic factor (BDNF) and neurotrophin 3 (NT-3) would protect auditory hair cells from ototoxicity by aminoglycoside antibiotic. Twenty-seven Wistar guinea pigs were divided into three groups of nine animals each. BDNF and NT-3 (100 microg/ml) were delivered into the right scala tympani of guinea pig cochlea through a cannula-osmotic pump device. Artificial perilymph (AP) was used as control. Immediately after implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…152 Indeed, the survival effects of BDNF on neuronal cells were not observed after the treatment phase. 155 This phenomenon has been widely confirmed by other studies in different neural systems, indicating that the survival effects of BDNF, as well as other growth factors only last so long as the treatment itself.…”
Section: Combinations With Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…152 Indeed, the survival effects of BDNF on neuronal cells were not observed after the treatment phase. 155 This phenomenon has been widely confirmed by other studies in different neural systems, indicating that the survival effects of BDNF, as well as other growth factors only last so long as the treatment itself.…”
Section: Combinations With Bdnfmentioning
confidence: 99%
“…Meanwhile, another study claimed that BDNF had no protective effect on HCs at 15 days (total 9 μg of BDNF) and 60 days (36 μg), but some effects at 30 days (18 μg). 152 One more study demonstrated that direct placement of 0.05 μg of BDNF into the inner ear after cochleostomy did not improve or treat hearing loss after cisplastin-induced deafening. 148 At the same time, the positive effect of 8.4 ng BDNF on SGCs survival in deaf guinea pigs has remained controversial in the context of dose-dependent manner of BDNF action.…”
mentioning
confidence: 99%
“…While, this approach is invasive and would be of considerable clinical risk, in experimental animal studies, the use of the osmotic pump has been demonstrated effective in the delivery of neurotrophic factors (Miller et al, 1997;Ylikoski et al, 1998;Ruan et al, 1999;Shoji et al, 2000a,b;Shinohara et al, 2002), viral vectors (Yagi et al, 1999), antioxidants (Yamasoba et al, 1998;Ohinata et al, 2000a,b), and transmitter antagonists (Ohinata et al, 2003;Puel et al, 1998;Jager et al, 2000). We have used this methodology in the recent demonstration of GCÕs effective protection of the inner ear from aminoglycoside ototoxicity (Himeno et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When given prior to or simultaneous to deafening, there is up to 95% survival of SGNs and hair cell protection (Ernfors et al, 1996;Ruan et al, 1999;Yagi et al, 1999;Suzuki et al, 2000). When given 4-7 days after deafening, 78-100% of SGNs survive (Staecker et al, 1996(Staecker et al, , 1998Miller et al, 1997;Yagi et al, 2000;Shinohara et al, 2002;Gillespie et al, 2003).…”
Section: Introductionmentioning
confidence: 99%